Inner experience differs in rumination and distraction without a change in electromyographical correlates of inner speech - Jamie Moffatt (PLoS ONE, 2020)
Ruminative thought is a style of thinking which involves repetitively focusing upon one’s own negative mood, its causes and its consequences. The negative effects of rumination are well-documented, but comparatively little is known about how rumination is experienced. The evaluative nature of rumination suggests that it could involve more inner speech than non-ruminative states. The present study (N = 31) combined facial electromyography and self-report questionnaires to determine the type of inner experience that occurs in rumination. The results showed that induced rumination involved similar levels of muscle activity related to inner speech as periods of induced distraction. However, experience sampling and questionnaire responses showed that rumination involved more verbal thought, and also involved more evaluative and dialogic inner speech than distraction. These findings contribute to the understanding of inner speech as a flexible phenomenon and confirms the importance of employing multiple methods to investigate inner speech. Future research should clarify the link between inner speech in rumination and its negative effects on wellbeing.